Induction of intestinal lesions in nu/nu mice induced by transfer of lymphocytes from syngeneic mice infected with murine retrovirus. Issue 2 (1st August 1997) - Suzuki, K; Narita, T; Yui, R; Ohtsuka, K; Inada, S; Kimura, T; Okada, Y; Makino, M; Mizuochi, T; Asakura, H; Fujiwara, M
Abstract : Background —Murine leukemia virus, LP-BM5, induces severe immunodeficiency with abnormal lymphoproliferation in susceptible C57BL/6 mice. In a previous study, it was shown that a Sjögren's syndrome-like systemic exocrinopathy is induced in the virus infected mice. Aims —To examine lymphocyte functions of the virus infected mice. Methods —Four-week old mice were inoculated with the virus and their spleen cells were transferred into syngeneic nu/nu mice. Their organs were examined by light and electron microscopy. Phenotypes of the colon infiltrating cells were examined by flow cytometry. Results —All nu/nu recipients had died by six weeks after cell transfer, showing runting disease like cachexia with diarrhoea and anal bleeding. Histopathological examination revealed that systemic exocrinopathy was adoptively transferable and that the colon became thickened due to mononuclear cell infiltration into the mucosal and submucosal layer with hyperplasia of intestinal epithelial cells. No virus particles were found in the colon. Flow cytometric analyses revealed that most of the infiltrating CD4+ T cells showed CD45RB low . No intestinal lesions were observed in the virus infected mice nor in nu/nu mice inoculated with normal lymphocytes. Conclusion —Lymphocytes of the virus infected mice induced colitis and hyperplasia of intestinal epithelial cells as well as systemic exocrinopathy in nu/nu mice. Our experimental system may give some insight into intestinal lesions associated with virus infection.